Cytophagic Histiocytic Panniculitis (CHP) in a Patient with SLE Found after Autopsy: When a Rash Is "Complicated!". (3rd July 2019) - Abbas, Hafsa; Aslam, Ahsan; Saad, Muhammad; Niazi, Masooma; Chilimuri, Sridhar
Abstract : Introduction . Cytophagic histolytic panniculitis (CHP) is a clinical disorder characterized by nodular panniculitis of the subcutaneous adipose tissue. It was first described in 1980 by Winkelmann. Histologically it is described as an infiltration of the adipose tissue by T- lymphocytes and phagocytic macrophages (also known as "bean bag cells"). Most of the cases are reported under the age of 50 and is a rare cause of panniculitis. We report a case of CHP in a young patient who presented to our emergency room (ER). Case Summary . A 39-year-old African American woman who presented to our hospital with lethargy, progressive confusion, and generalized rash involving both lower extremities of 1 week duration. She had a history of pancytopenia and focal proliferative and membranous lupus nephritis classes 3 and 5. Her physical examination was remarkable for bilateral lower extremity pitting edema and a desquamating rash on both of her legs. The Nicolsky sign was positive. She was noted to be hypotensive and was started on intravenous fluids and broad spectrum antibiotics. Routine laboratory tests revealed severe pancytopenia, with a hemoglobin of 3.9 g/dl, white blood cell count 600/ul, and platelet count of 11000/ul. Within an hour of arrival to the ER she developed acute respiratory failure. She was intubated and placed on mechanical ventilation. She developed shock requiring vasopressors. No imaging could be done due to her unstable condition. Four hours after her initial presentation she developed asystole and expired. Postmortem histopathology of the adipose tissue revealed CHP. Conclusion . CHP can be rapidly fatal. The treatment involves high dose of intravenous steroids and immunosuppressants such as cyclosporine.